Microscopic and magnetic properties of template assisted electrodeposited iron nanowires - Irshad, M.I. (American Institute of Physics Inc., 2015)
Nanowires of magnetic materials such as Iron, nickel, cobalt, and alloys of them are one of the most widely investigated structures because of their possible applications in high density magnetic recording media, sensor elements, and building blocks in biological transport systems. In this work, Iron nanowires have been prepared by electrodeposition technique using Anodized Aluminium Oxide (AAO) templates. The electrolyte used consisted of FeSO 4. 6H 2 O buffered with H 3 BO 3 and acidized by dilute H 2 SO 4 . FESEM analysis shows that the asdeposited nanowires are parallel to one another and have high aspect ratio with a reasonably high pore-filing factor. To fabricate the working electrode, a thin film of copper (â¼ 220 nm thick) was coated on back side of AAO template by e-beam evaporation system to create electrical contact with the external circuit. The TEM results show that electrodeposited nanowires have diameter around 100 nm and are polycrystalline in structure. Magnetic properties show the existence of anisotropy for in and out of plane configuration. These nanowires have potential applications in magnetic data storage, catalysis and magnetic sensor applications. Â© 2015 AIP Publishing LLC.